Evaluating the definition of severely injured patients: a Japanese nationwide 5-year retrospective study. Issue 2 (23rd February 2023) - Toida, Chiaki; Muguruma, Takashi; Gakumazawa, Masayasu; Shinohara, Mafumi; Abe, Takeru; Takeuchi, Ichiro
Abstract : Objectives: The definition of severely injured patients lacks universal consensus based on quantitative measures. The most widely used definition of severe injury is based on the Injury Severity Score (ISS), which is calculated using the Abbreviated Injury Scale in Japan. This study aimed to compare the prevalence, in-hospital mortality and OR for mortality in patients with ISS ≥16, ISS ≥18 and ISS ≥26 by age groups. Design: Retrospective cohort study. Setting: Japan Trauma Data Bank, which is a nationwide trauma registry with data from 280 hospitals. Participants: We used data of 117 199 injured patients from a national database. We included injured patients who were transferred from the scene of injury by ambulance and/or physician. Primary and secondary outcome measures: Prevalence, in-hospital mortality and OR for mortality with respect to age and injury level (ISS group). Results: In all age categories, the in-hospital mortality of patient groups with an ISS ≥16, ISS ≥18 and ISS ≥26 was 13.3%, 17.4% and 23.5%, respectively. The in-hospital mortality for patients aged >75 years was the highest (20% greater than that of the other age groups). Moreover, in-hospital mortality for age group 5–14 years was the lowest (4.0–10.9%). In all the age groups, the OR for mortality for patients with ISS ≥16, ISS ≥18 and ISS ≥26 was 12.8, 11.0 and 8.4, respectively. Conclusions: Our results revealed the lack of an acceptable definition, with a high in-hospital mortality and high OR for mortality for all age groups.